Bioethics in teaching of the discipline of human anatomy, in the professional school of medicine at the Jorge Basadre Grohmann University, Tacna - Rodríguez Menéndez, Abelardo (2023)
Human anatomy discipline has change, the use of the corpses, organs and natural specimens is necessary for teaching, surrounded of respect according to activities according to activities of high scientific-technical value for the educative influences. Also, the learning in the living organism, demands a responsible attitude from professor and students in bioethically, because of its most relation to the professional practice.The TIC is excellent didactic resource for the study of human anatomy, but it should have a place as complementary alternative for the use of anatomical pieces, model and other resources as the learning with living subject. The excessive and exclusive use in the medical education can carry a negative bioethical implication as the adjuvant factor of becoming medically inhuman, at the edge of technical problems in the learning.